1998
DOI: 10.1016/s0014-5793(98)00463-3
|View full text |Cite
|
Sign up to set email alerts
|

An intrinsically stable antibody scFv fragment can tolerate the loss of both disulfide bonds and fold correctly

Abstract: A fully functional cysteine-free derivative of the intrinsically stable anti-HER2 scFv fragment hu4D5^8 was generated by replacing the disulfide forming cysteine residues in V r and V v with the amino acid combination valine-alanine in both domains. The antigen binding properties, determined by ELISA and BIAcore measurements, were not affected by removal of the disulfide bonds. The thermodynamic stability of the disulfide-containing scFv of 8.1 kcal/mol is decreased upon complete reduction of both disulfides t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 39 publications
4
78
0
Order By: Relevance
“…Total RNA was extracted from the CD1d-transfected mouse RMA.S cell line using the RNeasy Mini Kit (QIAGEN). For the anti-HER2 antibody part, the plasmid pIG6-4D5, containing the scFv fragment derived from the mouse anti-HER2 antibody 4D5, was used as template (27) (kind gift from A. Pluckthun, University of Zurich, Zurich, Switzerland). Briefly, the entire mouse β2m was amplified with a Hind III site at the N-terminus for subsequent cloning in the PEAK 8 expression vector (EdgeBioSystems) and an Nhe I site at its C-terminus for its ligation to the N-terminal sequence of the a1 domain of CD1d, with the insertion of a sequence encoding a flexible glycine/serine-rich peptide linker (GGGGSGGSGSGGG).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total RNA was extracted from the CD1d-transfected mouse RMA.S cell line using the RNeasy Mini Kit (QIAGEN). For the anti-HER2 antibody part, the plasmid pIG6-4D5, containing the scFv fragment derived from the mouse anti-HER2 antibody 4D5, was used as template (27) (kind gift from A. Pluckthun, University of Zurich, Zurich, Switzerland). Briefly, the entire mouse β2m was amplified with a Hind III site at the N-terminus for subsequent cloning in the PEAK 8 expression vector (EdgeBioSystems) and an Nhe I site at its C-terminus for its ligation to the N-terminal sequence of the a1 domain of CD1d, with the insertion of a sequence encoding a flexible glycine/serine-rich peptide linker (GGGGSGGSGSGGG).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, to confer the tumor localization properties of the αGalCer/ sCD1d, we fused the β 2 m-CD1d molecule to an antitumor antibody fragment in view of our previous experience with tumor targeting of MHC class I coupled to different antitumor Fab′ fragments (25,26). To do so, a second (G 10 S 3 ) linker was inserted at the C-terminus of CD1d before ligation to the cDNA of the anti-HER2 4D5 scFv (27), followed by the same small linker (G 3 S 3 ) and His tag ( Figure 1A). Transient transfection of HEK293 EBNA cells adapted to grow in suspension in serum-free medium (28) gave similar yields for both recombinant CD1d proteins, alone or fused to the anti-HER2 scFv (up to 10 mg/l supernatant).…”
Section: Construction Expression and Purification Of Recombinant Momentioning
confidence: 99%
See 1 more Smart Citation
“…So far, only two artificial pairs (Val:Ala and Ala:Tyr) have been found to be functional replacements for the S-S bonds in Ig fold domains (3,40,43,44). It has also been reported that one of the Cys residues involved in an S-S bond can be replaced by Tyr, Ser, or Val (41,45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Many scFv cannot tolerate the loss of these disulfide bonds [107], and only a very few scFv constructs have been shown to fold correctly and retain their activity in the absence of intra-domain disulfide bonds [108,109]. Proba et al demonstrated that, although the stable ABPC48 scFv derived from its wild-type parental mAb is naturally missing a disulfide bond in the V H chain, restoration of the disulfide bond by point mutation can increase the stability of the scFv above that of the unmodified ABPC48 scFv [106].…”
Section: Stability Of Scfv Constructsmentioning
confidence: 99%